Developing Adaptive Bra Design For Woman With Hemiplegia: A Literature Review - Juliana, Dian; Feda Anisah Makkiyah (The Health Researcher's Journal, 2024)
Female stroke patients with hemiplegia will experience difficulties to not be able to use bras independently are due to weakness in the upper extremities. Meanwhile, the use of bras is very important for women because bras have a major function in maintaining breast shape by lifting the breasts. Therefore, this study aims to review developing adaptive bra design for woman with hemiplegia. The method of this study was a literature review. After screening stages, two studies are included in this review. Adaptive bra design for woman with hemiplegia is the development of a bra with modifications of material, design, and additional features, especially in the fasteners section by paying attention to good and comfortable materials for users. Some additional features can also be used either to monitor the physiological body of the user or in order to assist the use of the bra. A good adaptive bra design is a design that can help wear and remove the bra with one hand while still paying attention to comfort and aesthetic value.